Charged particle spectra obtained with the Mars Science Laboratory Radiation Assessment Detector (MSL/RAD) on the surface of Mars. Issue 3 (6th March 2014) - Ehresmann, Bent; Zeitlin, Cary; Hassler, Donald M.; Wimmer‐Schweingruber, Robert F.; Böhm, Eckart; Böttcher, Stephan; Brinza, David E.; Burmeister, Sönke; Guo, Jingnan; Köhler, Jan; Martin, Cesar; Posner, Arik; et al.
Abstract The Radiation Assessment Detector (RAD)—situated inside the Mars Science Laboratory's Curiosity rover—is the first ever instrument to measure the energetic particle radiation environment on the surface of Mars. To fully understand the influence of this surface radiation field in terms of potential hazard to life, a detailed knowledge of its composition is necessary. Charged particles are a major component of this environment, both galactic cosmic rays propagating to the Martian surface and secondary particles created by interactions of these cosmic rays with the atoms of the Martian atmosphere and soil. Here we present particle fluxes for a wide range of ion species, providing detailed energy spectra in the low‐energy range (up to several hundred MeV/nucleon particle energy), and integral fluxes for higher energies. In addition to being crucial for the understanding of the hazards of this radiation to possible future manned missions to Mars, the data reported here provide valuable input for evaluating and validating particle transport models currently used to estimate the radiation environment on Mars and elsewhere in space. It is now possible for the first time to compare model results for expected surface particle fluxes with actual ground‐based measurements.